(untitled) (Research, Society and Development, 2019)
We live in a technological world and full of constant changes, which is not distinctive when it comes to health. The enteroparasitoses are a serious problem and that has affected the population, mainly the citizens who do not have adequate hygienic-sanitary conditions. The objective of this article is to search for available evidence in the literature on the prevalence of epidemiological aspects of enteroparasitosis in children in Brazil. The study was carried out by means of a bibliographical review, through a survey of scientific articles using the main bases of scientific indexing, such as: Scielo and MedLine. The prevalence of enteroparositosis in Brazil is high, with social problems and partial access to public policies as collaborators in the spread of diseases, among them intestinal parasitoses, of which they occupy the top. Public health policies should be inserted and enjoyed by the unassisted community in these places, since children by virtue of their physiological conditions are more sensitive to such manifestations.